Foot Massage and Quranic Recitation for Pain Relief in Post-Cesarean Section Patients - Mellisa, Mellisa; Sumaryani, Sri; Wulandari, Noor (Inspirasi Foundation, 2025)
Introduction: Post-cesarean section pain is a common complication that may hinder maternal recovery, delay mobility, and disrupt early breastfeeding. While pharmacological treatments are available, non-pharmacological interventions such as foot massage and Quranic recitation have shown individual effectiveness in reducing pain. Objective: This study aimed to explore the combined effect of foot massage therapy and Quranic recitation (Surah Ar-Rahman) on the pain levels of post-cesarean section patients. Methods: A qualitative descriptive case study was conducted at RSUD Tidar Magelang from April 30 to May 7, 2025. Three primiparous Muslim women aged 20–35 years were selected through purposive sampling. Each participant received a 10–20-minute foot massage while simultaneously listening to Quranic recitation via headphones. Pain intensity was assessed using the Numeric Rating Scale (NRS) before and after the intervention over two consecutive days. Results: All participants initially reported moderate pain levels (NRS score of 5). After the intervention, pain levels decreased to mild (NRS score 2–3). Patients reported feeling calmer and more comfortable, attributing the relief to the synchronization of massage with spiritual recitation. These results align with existing literature supporting the effectiveness of both interventions individually. Conclusion: The combined application of foot massage and Quranic recitation effectively reduced postoperative pain in cesarean section patients. This culturally sensitive, non-pharmacological approach shows promise for holistic postpartum care, particularly in Muslim-majority settings. Further research with larger samples and control groups is needed to confirm its broader applicability and clinical significance.